1983
DOI: 10.1161/01.cir.68.6.1171
|View full text |Cite
|
Sign up to set email alerts
|

Results of endomyocardial biopsy in patients with spontaneous ventricular tachycardia but without apparent structural heart disease.

Abstract: To evaluate possible occult myocardial disease in 18 patients whose only major manifestation of heart disease was spontaneous ventricular tachycardia or fibrillation, right ventricular endomyocardial biopsies were performed. None of the patients had symptoms of ischemic or congestive heart disease, and at catheterization none had significant lesions of the coronary arteries or regional wall motion abnormalities of the left ventricle. The mean left ventricular ejection fraction (65 + 7%), mean right ventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
6

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(45 citation statements)
references
References 44 publications
2
37
0
6
Order By: Relevance
“…The predilection for fibrosis in the subendocardium of the NIZ is viewed as a significant contributory factor to mechanical dysfunction (29) and propensity for dysrhythmia (30) following MI. In the present study, in contrast to its neutral effect on fibrosis in the infarct zone, CA-074Me treatment significantly reduced ECM deposition in the areas remote from the site of infarction, particularly the subendocardial region, which was associated with a reduction in the level of in LV function.…”
Section: A B C D Ementioning
confidence: 99%
“…The predilection for fibrosis in the subendocardium of the NIZ is viewed as a significant contributory factor to mechanical dysfunction (29) and propensity for dysrhythmia (30) following MI. In the present study, in contrast to its neutral effect on fibrosis in the infarct zone, CA-074Me treatment significantly reduced ECM deposition in the areas remote from the site of infarction, particularly the subendocardial region, which was associated with a reduction in the level of in LV function.…”
Section: A B C D Ementioning
confidence: 99%
“…Many of these studies were conducted in the 1980s, and most involve only modest numbers of patients (Table 4). 144,[157][158][159][160][161][162] Most studies reported a high incidence of abnormal findings, although these were usually nonspecific findings; the incidence of histologically diagnosed myocarditis varied widely in these reports, and only rarely were other specific disease entities diagnosed. One authoritative review questioned the "strikingly high" incidence of reported histological myocardial abnormalities in the literature, and the review authors comment that they suspect the true incidence of abnormalities described in these reports to be lower.…”
Section: Clinical Scenario 13mentioning
confidence: 99%
“…This inferred that the presence of a low sympathetic threshold and/ or an arrhythmia-prone anatomic substrate was responsible for the occurrence of VT. Although 9 ofthe 14 patients had no clinically demonstrable heart disease, the possibility of their having subclinical cardiac diseases such as healed myocarditis and/or cardiomyopathy could not be excluded with certainty (65,66).…”
Section: Discussionmentioning
confidence: 99%